Analisis Makna Intensi Pada Puisi-Puisi Penyair Dunia: Analisis Puisi Karya M. Taslim Ali - Yani Suryani; Anisa Choir; Yuliana Ana Wana; Delis Nurpianti (ITB AAS INDONESIA Surakarta, 2021)
This paper is intended to see the meaning of the intention in the words of the poems written by students. The research method used in analyzing the descriptive qualitative research method. From the results of the poetry analysis, the author (student) as a beginner poet is very good at playing words to express the meaning of the poetry he writes. Line by line arranged in the verse is presented in its entirety so that it gives a meaningful message. Poetry text which is the author's thought is presented with easy-to-understand expressions and is packaged in such a way with cohesion and coherence. The poetry text is inseparable from the context and situation so that it makes the poetry more open. This also gives the understanding that poetry text is a form of real expression which is in process. Keywords: literary appreciation, student poetry, meaning of intention or intentionality, and the integrity of the text.